2008
DOI: 10.1016/j.bbrc.2008.06.069
|View full text |Cite
|
Sign up to set email alerts
|

Protection of retinal cells from ischemia by a novel gap junction inhibitor

Abstract: Retinal cells which become ischemic will pass apoptotic signal to adjacent cells, resulting in the spread of damage. This occurs through open gap junctions. A class of novel drugs, based on primaquine (PQ), was tested for binding to connexin 43 using simulated docking studies. A novel drug has been synthesized and tested for inhibition of gap junction activity using R28 neuro-retinal cells in culture. Four drugs were initially compared to mefloquine, a known gap junction inhibitor. The drug with optimal inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Morphological and ultrastructural studies in crayfish axons (122,123) and in rodent spinal cord, (124) both expressing Panxs, revealed small rosette-like GJ plaques that were completely different from the Cx GJ plaques, which have a bright punctate staining. Shestopalov and Panchin (4) hypothesized that these small rosette-like GJ plaques and the fine puncta observed in the Review article C. D'hondt et al Cx43: EC 50 ¼ 3 mM (90) 50 mM (104) IC 50 ¼ 2-4 mM (74) 10-100 mM (227) IC 50 ¼ 2-4 mM (74) 5-10% increase (229) Cx32: 100 mM Human/mouse Panx1: NE (229) Cx43: >10 mM (231) Flufenamic acid (FFA) 20-60 mM (235) Cx46 and 50: 3 mM (31, 236) 30 mM…”
Section: Structural Properties Of CX and Panx Channelsmentioning
confidence: 95%
See 1 more Smart Citation
“…Morphological and ultrastructural studies in crayfish axons (122,123) and in rodent spinal cord, (124) both expressing Panxs, revealed small rosette-like GJ plaques that were completely different from the Cx GJ plaques, which have a bright punctate staining. Shestopalov and Panchin (4) hypothesized that these small rosette-like GJ plaques and the fine puncta observed in the Review article C. D'hondt et al Cx43: EC 50 ¼ 3 mM (90) 50 mM (104) IC 50 ¼ 2-4 mM (74) 10-100 mM (227) IC 50 ¼ 2-4 mM (74) 5-10% increase (229) Cx32: 100 mM Human/mouse Panx1: NE (229) Cx43: >10 mM (231) Flufenamic acid (FFA) 20-60 mM (235) Cx46 and 50: 3 mM (31, 236) 30 mM…”
Section: Structural Properties Of CX and Panx Channelsmentioning
confidence: 95%
“…(86,177) n/a n/a PQ4 Cx43: 10 mM (231) n/a n/a n/a n/a Meclofenamic acid (MFA) Cx50: EC 50 ¼ 21 mM (226) NE (45) n/a n/a n/a Cx50: 100 mM (235) Arachidonic acid Cx43: 20 mM (259) n/a n/a n/a 4-5 mM (292) Cx43: EC 50 % 32 mM (250) Oleic acid Cx43: 20 mM (259) n/a n/a n/a n/a Cx43: EC 50 % 35 mM (250) Oleyl alcohol Cx43: EC 50 % 35 mM (250) n/a n/a n/a n/a Palmitoleic acid Cx43: EC 50 % 60 mM (250) Cx45: 50 mM (265) n/a n/a NE (265) Cx43: 50 mM (276) Cx 37 and 40: 50 mM (251) Stearic acid Cx43: EC 50 % 102 mM (250) n/a n/a n/a n/a Caprylic acid Cx43: EC 50 % 185 mM (250) n/a n/a n/a n/a (Continues) (32) indicating that glycosylation hinders GJ formation. Secondly, the preference of Panxs for hemichannel formation may also be an intrinsic property of these proteins.…”
Section: Structural Properties Of CX and Panx Channelsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26] Gap junction modulation has been identified as a potential neuroprotective target and recently it has been shown that gap junction inhibitors protect retinal neurosensory cells from ischemia in a cell culture model. 27 Connexin43 is the most abundant gap junction protein in the CNS and is primarily expressed on astrocytes. Alterations in connexin43 expression have been described following acute injury to the CNS [28][29][30][31][32][33][34] and in a variety of degenerative 35,36 and inflammatory diseases, 37 suggesting a role in the pathogenesis of neuronal damage.…”
Section: Introductionmentioning
confidence: 99%
“…In this scheme, toxic molecules are transferred intercellularly from dying cells to neighbors through communicating GJs, thereby producing a wave of ancillary cell degeneration (12,13). As the CNS locus with arguably the highest expression of GJs, bystander-mediated neuronal cell death in retina has been implicated in a number of pathologies, including excitotoxicity, retinitis pigmentosa, and ischemic retinopathy (12,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%